Influence of plant growth regulators on in vitro biomass production and biosynthesis of cytotoxic Amaryllidaceae alkaloids in Caliphuria tenera Baker (2023)
ABSTRACT: Plants of the Amaryllidoideae subfamily are characterized by the presence of isoquinoline alkaloids called Amaryllidaceae alkaloids. These compounds have exhibited a broad spectrum of pharmacological effects, including anti-Alzheimer and anti-cancer. In this study, Caliphruria tenera Baker, Amaryllidaceae, an endangered and endemic species, was selected to evaluate the effect of growth regulators on plant micropropagation, biomass increase, and production of cytotoxic alkaloids. Different growth regulators were used individually and mixed, and the Amaryllidaceae alkaloids were identified and quantified by GC-MS. The maximum number of in vitro shoots (4.8) was recorded with 6-benzylaminopurine (BAP) (1 mg/L) + Kinetin (KIN) (1 mg/L) + Naphthaleneacetic acid (NAA) (0.2 mg/L). In addition, nineteen alkaloids were identified as crinine, galantamine, lycorine, narciclasine, and tazzetine-type alkaloids in cultivated and micropropagated plants. In general, the biomass was maximized with the growth hormone combination BAP + KIN + NAA, but the biosynthesis of alkaloids was minimized. However, the combination BAP + NAA showed the greatest productivity of trisphaeridine (632.01 μg/g). The growth regulators showed also a positive effect on the production of lycorine-type alkaloids with a content of 396.33 μg/g for KIN, 142.38 μg/g for BAP, and 41.67 μg/g for NAA. All alkaloid fractions were evaluated for their antiproliferative effects against human lung carcinoma (A549) and human keratinocytes (HaCat) cells. The alkaloids produced in the BAP + NAA treatment present a potent and selective cytotoxic against the A549 cell line at 30 μg/mL. This study shows that micropropagation is a promising approach for the production of cytotoxic Amaryllidaceae alkaloids in C. tenera without affecting natural populations.